KCNQ1 Gene Variants in Large Asymptomatic Populations: Considerations for Genomic Screening of Military Cohorts. Issue 3 (1st March 2017) - Kruszka, Paul; Weiss, Karin; Hadley, Donald W.
ABSTRACT: Introduction: The advances in genomic technology of large populations make the potential for genomic screening of military cohorts and recruits feasible, affording the potential to identify at-risk individuals before occurrence of potentially life-threatening events. Exploring sudden cardiac death, known to cause significant morbidity and mortality in young military service members, we focused on the most common gene associated with long QT syndrome (LQTS), KCNQ1 . Materials and Methods: Using the publicly available database Exome Aggregation Consortium as a surrogate for a military population, variants in KCNQ1 were filtered on the basis of population prevalence, classification as a disease mutation in the Human Gene Mutation database, and classification as pathogenic or likely pathogenic in the ClinVar database. Variant prevalence and penetrance estimates were derived using reports from the medical literature. Results: We showed that in a population of over 60, 000 individuals, at least 97 (0.2%) individuals would harbor a potentially pathogenic mutation in KCNQ1, which is more prevalent than expected on the basis of current medical literature ( p = 0.0004). KCNQ1 variant penetrance was estimated to be only 9% to 17%. Identifying the importance of large genomic studies, our study demonstrates that 46% of pathogenic mutations in KCNQ1 had a population frequency of less than 1:50, 000. Conclusion: Screening a large database with genomic screening for a condition that is relevant to active duty service members results in the identification of many individuals with potentially pathogenic mutations in the KCNQ1 gene, which has profound implications for screening military or other adult cohorts in terms of over diagnosis, overtreatment, and increased medical resource usage. This study of KCNQ1 provides a platform for consideration of other genes that cause sudden cardiac death as well as other medically actionable hereditary disorders for which genomic screening is available. We review the potential benefits of genomic screening and also present the complex hurdles that will be encountered as such technologies unfold.